Gas conditioning in H2 rich syngas production by biomass steam gasification: Experimental comparison between three innovative ceramic filter candles. (22nd June 2015) - D'Orazio, A.; Rapagnà, S.; Foscolo, P.U.; Gallucci, K.; Nacken, M.; Heidenreich, S.; Di Carlo, A.; Dell'Era, A.
Abstract: The biomass steam gasification is a promising path to obtain hydrogen-rich syngas and to improve the global efficiency for cogeneration purposes. The present study reports the results of a campaign of steam gasification tests performed in a bench-scale gasifier (0.1 m ID) housing in its freeboard a ceramic filter, in a temperature range of 800 °C–815 °C. Three new ceramic filters have been tested: (i) noncatalytic candle with new support, (ii) filter candle with catalytic layer, (iii) filter candle with new integrated catalytic foam system and results were compared to those obtained in tests without candle. The volume composition of the syngas was monitored and analyzed by online measurement by means of infrared – thermal conductivity detector (IR-TCD) facilities to evaluate the CO, CO2, CH4, H2, NH3 composition. The Topping Atmosphere Residue (tar) content was evaluated by gas-chromatograph mass spectrometer (GCMS) facility; gas yield, water conversion and char conversion were also calculated from direct measurements. The best results were obtained in the case of innovative catalytic filter in association with cycled olivine bed, obtaining gas yield equal to 1.80 Nm 3 /kgdaf (vs 1.00 Nm 3 /kgdaf without candle); observed to theoretical water conversion ratio equal to 0.88 (vs 0.33); H2 volume content equal to 56% (vs 39%); total tar content equal to 0.14 g/Nm 3 (vs 6 g/Nm 3 ). Highlights: Gas conditioning in H2 rich syngas production by biomass steam gasification. Three innovative ceramic filter candles are experimentally compared. Hydrogen content close 56% in the product gas is achieved. Gas yield equal to 1.80 Nm 3 /kgdaf and good water conversion are obtained. Optimal performance of catalytic candle integrated with catalytic foam is proven.